Program PECS (Picture Exchange Communication System) untuk Meningkatkan Kemampuan Berbicara Terstruktur pada Anak Autis - Restu Vistasari; Bhina Patria (Faculty of Psychology, Universitas Gadjah Mada, 2019)
Most children with autism have difficulty with their communication skill. One of the specific problems is about to combine words into structured sentences when they tried to speak. The purpose of this research was to examine the efficacy of PECS in improving structured language skills to children with autism. Participants of this research consisted of two children who have been diagnosed with autism. The dependent variable of this study was structured language skill in speaking and the independent variable of the study was The PECS Program which had been modified in some phases. The method that was used in this study is single-case research with A-B-A design. Behavior checklist was used as the instrument for this research, also data of this research were analyzed by visual inspection. The result of the visual inspection analysis showed that there were some improvements in grammatical language skills of the participants throughout the PECS program.